A high-performance tri-electrolyte aluminum-air microfluidic cell with a co-laminar-flow-and-bridging-electrolyte configuration. (1st February 2022) - Feng, Shan; Yang, Guandong; Zheng, Dawei; Rauf, Abdur; Khan, Ubaid; Cheng, Rui; Wang, Lei; Wang, Wentao; Liu, Fude
Highlights: A novel tri-electrolyte aluminum-air microfluidic cell is firstly reported. The cell structure combines a bridging electrolyte with the co-laminar flow. The cell shows both high ion exchange efficiency and electrical output stability. The power density is up to 189.22 mW cm −2 which only decays 4.69% after 10 cycles. The evaluated accumulated electrolyte utilization is up to 66.07% at cell cycle 90. Abstract: The aluminum-air cell is one of the most promising candidates for next-generation power sources due to its high theoretical energy density. In particular, a tri-electrolyte aluminum-air cell shows high stability and cell voltage. However, the output power density is limited because of the increased internal resistance. Here, we demonstrate a tri-electrolyte aluminum-air microfluidic cell, which takes advantages of the bridging electrolyte and the co-laminar flow to separate the alkaline anolyte from the acidic catholyte. The novel cell structure helps to maintain high ion exchange efficiency, minimize the electrolyte neutralization, and improve the cell stability. The short-circuit current density and maximum power density at the first electrolyte cycle are up to 367.46 mA cm −2 and 189.22 mW cm −2, respectively; after 10 electrolyte cycles, the variation is less than 2.85% and 4.69%, respectively. The cell internal resistivity is 5.42, 5.41, and 5.55 Ω cm 2 at cycle 1 under flow rates of 0.5, 1.0 and 2.0 ml min −1, respectively, which demonstrates the cell stability under flowing electrolytes. An integrated cell system assembled with 24 cells is further fabricated and evaluated. The short-circuit current only drops to half at cell electrolyte cycle 156 theoretically. Therefore, this work provides an alternative strategy for economical and long-lasting aluminum-air cells as less-frequent power sources.